Shear Strength Characteristics of Calcium Oxide and Guar Gum Treated Loose Petobo Silty Sand - Montol, Yohanes Albrecht; Lim, Aswin; Rahardjo, Paulus Pramono (Journal of Applied Engineering and Technological Science (JAETS), 2024)
This article presents the shear strength characteristics of Petobo Silty Sand which are treated with Calcium Oxide and Guar Gum. The purpose of this experimental works is looking for other binding agents to replace the application of cement which is considered not an environmentally friendly material. The shear strength of treated soils was examined using the direct shear test. Guar gum and Calcium Oxide provides additional cohesion to Petobo silty sand. The cohesion and internal friction angle could increase to about 900 kPa and 47.5°, respectively. The treated sample also shows the dilation behavior in dry conditions. However, after 24 hours soaking period, the soil behavior returned to the contraction behavior. This behavior is unfavorable in the case of the treated sample below the groundwater table. Hence, these two binding agents are effective for dry soil conditions. In addition, Scanning Electron Microscope images of treated silty sand were obtained which aims to examine the microscopic behavior of the fibers and matrices that were formed through the hydration process.